An omics investigation into chronic widespread musculoskeletal pain reveals epiandrosterone sulfate as a potential biomarker. Issue 10 (October 2015) - Livshits, Gregory; Macgregor, Alexander J.; Gieger, Christian; Malkin, Ida; Moayyeri, Alireza; Grallert, Harald; Emeny, Rebecca T.; Spector, Tim; Kastenmüller, Gabi; Williams, Frances M.K.
Abstract : Abstract: Chronic widespread musculoskeletal pain (CWP) is common, having a population prevalence of 10%. This study aimed to define the biological basis of the CWP/body mass association by using a systems biology approach. Adult female twins (n = 2444) from the TwinsUK registry who had extensive clinical, anthropometric, and "omic" data were included. Nontargeted metabolomics screening including 324 metabolites was carried out for CWP and body composition using dual-energy X-ray absorptiometry. The biological basis of these associations was explored through a genome-wide association study and replicated in an independent population sample (Cooperative Health Research in the Region of Augsburg [KORA] study, n = 2483). A causal role for the genetic variants identified was sought in CWP using a Mendelian randomisation study design. Fat mass/height 2 was the body composition variable most strongly associated with CWP (TwinsUK: P = 2.4 × 10 −15 and KORA: P = 1.59 × 10 −10 ). Of 324 metabolites examined, epiandrosterone sulfate (EAS) was highly associated with both CWP ( P = 1.05 × 10 −09 in TwinsUK and P = 3.70 × 10 −06 in KORA) and fat mass/height 2 . Genome-wide association study of EAS identified imputed single nucleotide polymorphism rs1581492 at 7q22.1 to be strikingly associated with EAS levels ( P ⩽ 2.49 × 10 −78 ), and this result was replicated in KORA ( P = 2.12 × 10 −9 ). Mendelian randomization by rs1581492 genotype showed that EAS is unlikely to be causally related to CWP. Using an agnostic omics approach to focus on the association of CWP with body mass index, we have confirmed a steroid hormone association and identified a genetic variant upstream of the CYP genes, which likely controls this response. This study suggests that steroid hormone abnormalities result from pain rather than causing it, and EAS may provide a biomarker that identifies subgroups at risk of CWP. Abstract : An "omics" investigation of chronic widespread pain in 2 population samples reveals a genetic variant in CYP3A5 as underlying steroid hormone abnormalities seen in CWP.